Text and the city essays on Japanese modernity - Maeda, Ai 1932-1987 (Duke University Press, 2004)
Foreword: A Walker in the City: Maeda Ai and the Mapping of Urban Space HARRY HAROOTUNIAN -- Introduction: Refiguring the Modern: Maeda Ai and the City JAMES A. FUJII -- LIGHT CITY, DARK CITY: VISUALIZING THE MODERN -- 1. Utopia of the Prisonhouse: A Reading of In Darkest Tokyo -TRANSLATION BY SEIJI M. LIPPIT AND JAMES A. FUJII -- 2. The Panorama of Enlightenment TRANSLATION BY HENRY D. SMITH -- 3. The Spirits of Abandoned Gardens: On Nagai Kafū's "The Fox" TRANSLATION BY WILLIAM F. SIBLEY -- PLAY, SPACE, AND MASS CULTURE -- 4. Their Time as Children: A Study of Higuchi Ichiyō̄'s Growing Up (Takekurabe) TRANSLATION BY EDWARD FOWLER -- 5. Asakusa as Theater: Kawabata Yasunari's The Crimson Gang of Asakusa TRANSLATION BY EDWARD FOWLER -- 6. The Development of Popular Fiction in the Late Taishō Era: Increasing Readership of Women's Magazines TRANSLATION BY REBECCA COPELAND -- TEXT, SPACE, VISUALITY -- 7. From Communal Performance to Solitary Reading: The Rise of the Modern Japanese Reader TRANSLATION BY JAMES A. FUJII -- 8. Modern Literature and theWorld of Printing TRANSLATION BY RICHARD OKADA -- CROSSING BOUNDARIES IN URBAN SPACE -- 9. Ryūhoku in Paris TRANSLATION BY MATTHEW FRALEIGH -- 10. Berlin 1888: Mori Ōgai's "Dancing Girl" TRANSLATION BY LESLIE PINCUS -- 11. In the Recesses of the High City: On Sōseki's Gate TRANSLATION BY WILLIAM F. SIBLEY -- Afterword WILLIAM F. SIBLEY
Includes bibliographical references and index
Keywords: Japanese literature / History and criticism / 1868-; Cities and towns in literature; Space and time in literature